Warped Discrete Cosine Transform-Based Low Bit-Rate Block Coding Using Image Downsampling. (3rd April 2007) - Ertürk Ertürk, Sarp Sarp
Abstract : This paper presents warped discrete cosine transform (WDCT)-based low bit-rate block coding using image downsampling. While WDCT aims to improve the performance of conventional DCT by frequency warping, the WDCT has only been applicable to high bit-rate coding applications because of the overhead required to define the parameters of the warping filter. Recently, low bit-rate block coding based on image downsampling prior to block coding followed by upsampling after the decoding process is proposed to improve the compression performance for low bit-rate block coders. This paper demonstrates that a superior performance can be achieved if WDCT is used in conjunction with image downsampling-based block coding for low bit-rate applications.